2021
DOI: 10.2174/1570163816666191105162722
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera in Malnutrition: A Comprehensive Review

Abstract: : Nutritional deficiency is a major concern in developing countries resulting in serious health consequences like mental and physical growth retardation. Moringa oleifera(Moringa), a nutritious plantgrowing in tropical regions of developing countries, is a candidate for overcoming nutritional deficiency. Moringa leaves are rich in protein including Sulphur containing amino acids.It contains high amounts of vitamin C than oranges, higher concentration of vitamin A than carrots, higher calcium content than milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Because moringa leaves contain 25 times more iron than spinach, they can also improve breast milk quality in addition to their high nutritional value (Rockwood et al 2013). Moringa oleifera L., commonly known as moringa, is a plant with high nutritional value and has the potential to address nutritional deficiencies effectively (Mushtaq et al 2021, Rode et al 2022. The leaves of Moringa oleifera L., commonly known as moringa, are rich in nutrients and known to enhance the production of breastmilk.…”
Section: Resultsmentioning
confidence: 99%
“…Because moringa leaves contain 25 times more iron than spinach, they can also improve breast milk quality in addition to their high nutritional value (Rockwood et al 2013). Moringa oleifera L., commonly known as moringa, is a plant with high nutritional value and has the potential to address nutritional deficiencies effectively (Mushtaq et al 2021, Rode et al 2022. The leaves of Moringa oleifera L., commonly known as moringa, are rich in nutrients and known to enhance the production of breastmilk.…”
Section: Resultsmentioning
confidence: 99%
“…Tese components are illustrated in Table 4. Te plant parts contain a high amount of sulphur-containing amino acids, and they contain higher amounts of β-carotenes than carrots, higher amounts of L-ascorbate than oranges, higher levels of calcium than milk, higher potassium levels than that in bananas, nine times more iron than that in spinach, and four times more fber than that in oats [110]. Other functional chemical groups have been extracted from leaves such as aldehydes, acids, amides, alcohols, phenols, vitamins, and phytosterols [111].…”
Section: Moringa Oleiferamentioning
confidence: 99%
“…(1) Moringa oleifera and Calcium. MO is approved to contain higher Ca than milk and more potassium (K) than that in bananas [110,233]. Many methods could be used for the formulation and extraction of MO to increase its bioaccessibility and bioavailability of Ca [234].…”
Section: Moringa Oleifera and Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last few decades moringa has been studied extensively to use it in food fortification. Dried leaves of moringa have been processed to produce herbal tea which retains better nutritional and sensory qualities than other herbal tea [11] . A study in Greece showed that herbal tea prepared from M.oleifera dried leaves had a great antioxidant activity due to flavonoles and total phenol contents [12] .…”
Section: Recent Researchmentioning
confidence: 99%